GR_GERICHTE ZR2 2025 19 vom 24. Juli 2025 , Ersitzung einer Dienstbarkeit - GR Gerichte (2025)
azione di accertamento dell'inesistenza del debito (art. 85a LEF) | OR 552-926 AG/andere Handelsgesellschaft/Genossenschaft